Government Procurement and Contracting. hearings before the United States House Committee on Government Operations, Subcommittee on Military Operations, Ninety-First Congress, first session, on Mar. 25-27, 1969. (U.S. Congressional Hearings., 1969)
Considers (91) H.R. 474.